Vulnerability to coastal flood hazard of residential buildings on Noirmoutier Island (France). Issue 2 (14th March 2016) - Creach, Axel; Chevillot-miot, Elie; Mercier, Denis; Pourinet, Laurent
Abstract : Storm Xynthia was responsible for the death of 41 people by drowning after the flooding by the sea of low-lying areas along French Atlantic coast in February 2010. This toll was partly explained by inadequacy of houses to flood hazard: 78% of the deaths occur in single-storey constructions. In this paper, we propose a map linking architectural typology of constructions with potential water depth in case of coastal flood event. The goal is to identify residential houses which present a high level of vulnerability for people to a potential coastal flood event. This work is presented on Noirmoutier Island which was few impacted by Storm Xynthia. However, it presents some common points with the most hit territories during the storm: 70% of the territory is under Xynthia level; 65% of the houses located in this low-lying area are single-storey constructions This map shows us different vulnerability between the four towns of the island.